Penyelesaian Hukum Atas Laporan Pelanggaran Perilaku Oleh Notaris - Tiara Indah Safitri (Officium Notarium, 2021)
This study aims to analyze the authority of the Notary Supervisory Board (MPN) and the Notary Honorary Council (DKN) for alleged violations of Notary behavior and legal settlements related to behavioral violations by Notaries. This research is an empirical juridical research, namely legal research on the enforcement or implementation of normative legal provisions in real behavior in every legal event that occurs in society. The results of the study concluded that the authority of MPN and DKN for alleged violations of Notaries in general can be said to have the same duties and authorities, namely carrying out the supervisory function of Notaries. However, upon further inspection, there is a difference between the Notary Supervisory Council and the Notary Honorary Council, namely MPN is a Notary supervision organization formed by the government, in this case the Ministry of Law and Human Rights of the Republic of Indonesia while DKN is a Notary supervision organization formed by the Indonesian Notary Association (INI)Key Word: Notary position, Notary supervision, supervisory authority AbstrakPenelitian ini bertujuan untuk menganalisis mengenai kewenangan Majelis Pengawas Notaris dan Dewan Kehormatan Notaris atas dugaan pelanggaran perilaku Notaris dan penyelesaian hukum terkait dengan pelanggaran perilaku oleh Notaris. Penelitian ini adalah penelitian yuridis empiris, yaitu penelitian hukum mengenai pemberlakuan atau implementasi ketentuan hukum normatif secara perilaku nyata pada setiap peristiwa hukum yang terjadi dalam masyarakat. Hasil penelitian menyimpulkan bahwa kewenangan MPN dan DKN atas dugaan pelanggaran Notaris secara garis besar dapat dikatakan memiliki tugas dan kewenangan yang sama, yakni menjalankan fungsi pengawasan terhadap Notaris. Namun apabila diperhatikan lebih lanjut, terdapat perbedaan antara Majelis Pengawas Notaris dengan Dewan Kehormatan Notaris, yakni MPN merupakan organisasi pengawasan Notaris yang dibentuk oleh pemerintah, dalam hal ini Kemenkumham RI sedangkan DKN merupakan organisasi pengawasan Notaris yang dibentuk oleh Perkumpulan Ikatan Notaris Indonesia (INI).Kata-kata Kunci: Jabatan Notaris, pengawasan Notaris, kewenangan pengawasan